Universal newborn hearing screening program – success story or a burden: experience from a tertiary care centre in North India - Bhatnagar, Akshay; Shyamlal, Yadav S.; Rizvan, Ahmad; Nayyar, Supreet S.; Tripathi, Shailendra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Aim of the study was to find out the prevalence of congenital hearing loss in a tertiary care hospital in North India under the Universal Neonatal Hearing Screening Program, with a specific focus on identifying the association between neonatal hearing loss and neonatal intensive care unit (NICU) admission, low birth weight, or advanced maternal age. Methods: A prospective cohort study of all newborns in a tertiary care center over 1.5 years. Results: A total of 2891 babies were born during the study period, of which 2693 underwent newborn hearing screening, of which 2.4% (n=7) were detected to have neonatal hearing loss. Among the neonates admitted to NICU (n=76), a total of 2.7% (n=2) were confirmed to have hearing loss. None of the babies with low birth weight or with a history of advanced maternal age (>35 years) were detected to have hearing loss. Conclusions: Our study primarily dealt with evaluating the key outcomes of a universal hearing screening program utilizing distortion product otoacoustic emission (DPOAE) and brainstem evoked response audiometry (BERA). NICU admission was identified as a specific neonatal risk factor correlating to hearing impairment (2.7%), with minimal or no correlation between low birth weight and increased maternal age.